Pengaruh Utilitarian Value, Hedonic Value, Citra Merek Terhadap Keputusan Pembelian - Muhammad Alfiansyah; RA Nurlinda (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study examines and analyzes the effect of utilitarian value, hedonic value, brand image simultaneously and partially on purchasing decisions. And knowing which variable is the most dominant in influencing purchasing decisions. The research approach used in this research is quantitative research. The criteria for selecting the sample in this study were those aged 17 and over who had bought and used a Charles & Keith bag for more than 1 year and were in the Greater Jakarta area. Questionnaires were collected as many as 165 respondents, the data was then processed using multiple linear regression method. Based on the results of the analysis it is known that the variables utilitarian value, hedonic value, brand image simultaneously have a positive effect on purchasing decisions. Partially the utilitarian value, hedonic value, brand image variables have a positive effect on purchasing decisions. Furthermore, the results show that the brand image variable is the most dominant variable influencing purchase decision.